Catalytic Oxidation of Silyl Enol Ethers to 1,2-Diketones Employing Nitroxyl Radicals - Hayashi, Masaki; Shibuya, Masatoshi; Iwabuchi, Yoshiharu (Synlett, 2012)
A novel and efficient method for the preparation of 1,2-diketones is reported. A series of α-diketones were readily prepared by the nitroxyl-radical-catalyzed oxidation of silyl enol ethers using magnesium monoperoxyphthalate hexahydrate (MMPP⋅6H2O) as the co-oxidant.
Keywords: oxidation; catalysis; enols; diketones; nitroxyl radical